1974
DOI: 10.1055/s-0028-1108170
|View full text |Cite
|
Sign up to set email alerts
|

Frühdiagnose und Häufigkeit der familiären Hyperlipoproteinämie Typ II

Abstract: Die frühe Diagnose der familiären Hyperlipoproteinämie vom Typ II a ist aus präventivmedizinischer Sicht von entscheidender Bedeutung. Um festzustellen, ob diese genetisch bedingte Stoffwechselerkrankung bereits bei der Geburt diagnostiziert werden kann, wurden 1323 Neugeborene in Südwestdeutschland untersucht, und nach einem Jahr wurde eine Verlaufskontrolle durchgeführt. Der Normbereich für das Gesamtcholesterin im Nabeischnurblut der Neugeborenen betrug 40-100 mg/dl, der des -ChoIesterins 15-60 mg/dl. Bei 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
4
8
0
Order By: Relevance
“…The interest in making an early diagnosis has to do with the theoretical benefit in reducing the increased risk of premature coronary heart disease by early dietary and pharmaceutical intervention. Five studies (1,2,4,25,26) have shown that measurement of cord serum T-C alone does not discriminate newborns with FH . This is probably due to the fact that most of the cord serum T-C is not transported by the LDL-but by the HDLfraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interest in making an early diagnosis has to do with the theoretical benefit in reducing the increased risk of premature coronary heart disease by early dietary and pharmaceutical intervention. Five studies (1,2,4,25,26) have shown that measurement of cord serum T-C alone does not discriminate newborns with FH . This is probably due to the fact that most of the cord serum T-C is not transported by the LDL-but by the HDLfraction.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the fact that most of the cord serum T-C is not transported by the LDL-but by the HDLfraction. Four studies (1)(2)(3)(4) have shown that an elevation of cord serum LDL or VLDL+ LDL will give a suspicion of FH in the child, but only one study (I) has unambiguously shown that an elevated cord serum LDL-C combined with a follow-up study after year one in a child with known FH in one parent allows a diagnosis of FH. In children with unknown parental phenotypes the three existing studies have been incomplete and inconclusive as for estimation of incidence of FH and false positive and negative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have focused on cholesterol and LDL (low density lipoprotein). Kwiterovich et al ( I ) , Greten et al (2), and Andersen & Friis-Hansen (3) have shown that elevated cord serum LDL or LDL-cholestercl indicates, that the newborn infant suffers from familial type I1 hyperlipoproteinemia, characterized by severe hypercholesterolemia, xanthomas and a risk of early ischemic heart-disease (for heterozygous males in their thirties or forties). Furthermore, the studies by Glueck et al (4,5) have suggested that early treatment may be beneficial by lowering the serum cholesterol in these children.…”
mentioning
confidence: 99%
“…Several papers have dealt with cord blood cholesterol estimations and the mean values reported ränge from 60 to 82 mg/dl in the studies published between 1970 and 1977 [7,8,10,11,12,13,15,18,20]. According to MISHKEL [17], this discrepancy is due to various (ethnic, nutritional, geographical, etc.)…”
Section: Cholesterol and Total Lipidsmentioning
confidence: 94%